A computational approach to the psychiatric diagnosis - Carrillo, Facundo (2016)
One of the most important aims of computational psychiatry (CP) is to provide computational tools to help with earlier diagnoses in psychiatric disorders. CP implements different computer science tools to assist the medical professional in the path to the diagnoses. The paradigm where CP works is to understand the patient as a producer of data from differents cognitive levels. These data could come from physiological studies (as functional magnetic resonance imaging or electroencephalography) or from more abstract levels like patients' thoughts. In our research line, we use spontaneous speech as source as a window into the patient's minds.